Prediction of "greening" on steam cooked tuna fish based on the trimethylamine, pH and soluble proteins content of the raw tuna fish - Rillo, Belen O.
Random samples of fresh yellowfin tuna were taken for analyses of pH, trimethylamine and soluble proteins content. The samples were steam cooked and evaluated for color and texture. The correlation coefficients ad coefficient of variation between pH, trimethylamine and soluble proteins content of the raw fish and color and texture of the cooked fish were computed and presented. "Greening" in stem cooked tuna fish, a measured by Munsell values and color scores, was significantly correlated with pH and trimethylamine of the raw fish samples but poorly correlated with soluble proteins content. Textures score also gave a poor correlation with pH, trimethylamine and soluble proteins content. Raw tuna meat with pH values up to 5.8 and trimethylamine values up to 4.99 mg % gave a cooked meat with normal pinkish to slight brown color, while pH values up to 6.1 and trimethylamine values of 9 mg % and above resulted in "green" tuna.